Pengaruh Struktur Kepemilikan Perusahaan Pada Kinerja: Faktor Ketidakpastian Lingkungan Sebagai Pemoderasi - Muchammad Syafruddin (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2006)
Besides examining strong relationship between outside ownership concentration and organizational performance, based on the agency theory, theoreticians in financial field also sug¬gest that there is a contradictory relationship between insider ownership and organizational performance. Past empirical studies showed that the insider ownership and organizational performance have not firmly established this relationship. On the basis of the contingency theory and agency theory, the current study postulates and tests the impact of environmental uncertainty on the insider ownership and performance nexus. The study finds that estimation results support the hypothesis that there is significantly positive relationship between outside ownership concentration and organizational performance. The estimation results also show that there is significant positive impact of environmental uncer¬tainty on the insider ownership and firm's performance, but insider ownership factor alone is not significantly influencing firm’s performance.Keywords: outside ownership concentration, insider ownership, environmental uncer¬tainty, organ¬izational performance, agency theory, contingency theory.